Dinamika dan Evolusi Pantai Probolinggo, Jawa Timur - Suyarso (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Dynamics and Evolution of the Coast of Probolinggo, East Java. The coastal plain of Probolinggo extends from Tongas Subdistrict in the western part to Kraksaan Subdistrict in the eastern part. The south side is the fertile rice field area, while the north side is the fish pond area. The phenomena of coastal changes in Probolinggo are strongly influenced by the materials supplied from Mount Bromo. This research was conducted in April–May 2012, February 2013, and August 2014 and aimed to gain insight into the coastal dynamics and evolution as well as changes and land cover convertion in Probolinggo. The analysis of coastal changes in Probolinggo from 1973 until 2013 was done using multitemporal landsat imageries, the measurement and drawing of coastal profile were carried out using shokiza geodetic instrument and SeaBird Electronic tide gauge. The results showed that in the western part, the accretion process is still ongoing, while in the eastern part, the accretion speed since 1989 has continued to decline and even some places experienced erosion. The new coastal plain formed by the accretion of marine processes is utilized by the residents as fish ponds, whereas accretion formed by fluvial processes is utilized as rice fields.